GREETINGS VARIETY TO SHOW POLITENESS IN GORONTALO LANGUAGE - Dewi Dama (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract This research aims to present the forms of greetings in Gorontalo Language and the examples used in society. The study focused on the use of Gorontalo language and took place in Ayula Tilango Kecamatan Bulango Selatan. The data were obtained through observation and elicitation. The results indicated various greetings based on Based on the findings, in Bahasa Gorontalo, there are, namely: Name in the form of kinship relationship (family connection – Vertically), name in the form of horizontal relationship (intimacy, friendship and body shape), name has a collective identifying character of the clan / fam (surname), name with religious title, name contains a custom title or an honors degree (given for personal achievements, a hero or died important person, important status in local government), and name contains a noble title. Keywords: Greetings, naming, titles, Gorontalo Language.